Impact of Motivation on Teachers’ Productivity in Public Secondary Schools in Zaria Local Government, Kaduna State - Yakubu, Iliya (International Journal of Human Kinetics, Health and Education, 2023)
The study explored the impact of motivation on teachers’ productivity in public secondary schools in Zaria Local Government in Kaduna State. This study was set out to find out the impact of regular payment of salary on teachers’ productivity in public secondary schools in Zaria Local Government in Kaduna State; and to determine the impact of in-service training on teachers’ productivity in public secondary schools in Zaria Local Government in Kaduna State. These objectives were transcribed into two research questions and two hypotheses respectively. The study employed the use of survey research design. The target population of the study was made up of 46 principals, 1183 teachers and 12 education officials from Zaria Local Government Area, Kaduna State. A sample size of 9 principals, 237 teachers and 2 education officials, totalling 248 respondents were used in the study. The study sample size represented 20% of the entire population drawn using random sampling technique. The instrument titled ―motivation and teachers’ productivity questionnaire (MTPQ)‖ was used for data collection in the study. The instrument was pilot tested and reliability coefficient of 0.84 was obtained. The data collected in study was analysed using descriptive statistics of frequency, mean and standard deviation to answer the research questions, while Pearson Product Moment Correlation statistics was used to test the hypotheses at 0.05 level of significance. Findings of the study showed that regular payment of salary results in high teachers’ productivity in public secondary schools in Zaria Local Government in Kaduna State; and Sponsorship toundertake in-service training improve teachers’ productivity in public secondary schools in Zaria Local Government in Kaduna State. Based on the findings of the study, it was recommended among others that Kaduna State Government should always try as much as possible to pay teachers’ salaries promptly and regularly. There should be regular training of teachers through workshops and refresher courses to motivate them for higher productivity.